Media Adaptation of Mask Making in Malang: Study of Functional and Process for Making Fiber Masks - Izam Ismail (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2021)
The mask is the main attribute in Malang Mask Show. The representation of Malang masks has undergone adaptation along with the development of the times, which were originally made of wood. This study aims to analyze the Malang mask material from the adaptation process of fiber raw materials as its component. The research approach method is descriptive qualitative. Data collection techniques using observation and interviews as the unit of analysis descriptively. The results of the study on the adaptation of the raw material for making Malang masks from wood into fiber as a medium of learning and the preservation of local culture as a medium of learning in schools. The technique of making Malang masks with fiber material uses the basic principles of printing and finishing techniques in the painting process using acrylic paint. An important finding from this research is that the Malang Mask making material using fiber has long durability, does not rot because it is synthetic